A Unified Breaking Onset Criterion for Surface Gravity Water Waves in Arbitrary Depth. Issue 7 (19th July 2020) - Derakhti, Morteza; Kirby, James T.; Banner, Michael L.; Grilli, Stephan T.; Thomson, Jim
Abstract: We investigate the validity and robustness of the Barthelemy et al. (2018, https://doi.org/10.1017/jfm.2018.93 ) wave‐breaking onset prediction framework for surface gravity water waves in arbitrary water depth, including shallow water breaking over varying bathymetry. We show that the Barthelemy et al. (2018) breaking onset criterion, which they validated for deep and intermediate water depths, also segregates breaking crests from nonbreaking crests in shallow water, with subsequent breaking always following the exceedance of their proposed generic breaking threshold. We consider a number of representative wave types, including regular, irregular, solitary, and focused waves, shoaling over idealized bed topographies including an idealized bar geometry and a mildly to steeply sloping planar beach. Our results show that the new breaking onset criterion is capable of detecting single and multiple breaking events in time and space in arbitrary water depth. Further, we show that the new generic criterion provides improved skill for signaling imminent breaking onset, relative to the available kinematic or geometric breaking onset criteria in the literature. In particular, the new criterion is suitable for use in wave‐resolving models that cannot intrinsically detect the onset of wave breaking. Key Points: The breaking onset criterion developed by Barthelemy et al. (2018) is shown to be applicable to waves breaking in shallow water The new criterion is suitable for use in wave‐resolving models that cannot intrinsically detect the onset of wave breaking The LES/VOF code is shown to provide accurate descriptions of conditions at steep wave crests